Outcomes of Revascularized Acute Mesenteric Ischemia in the American College of Surgeons National Surgical Quality Improvement Program Database - NEWTON, WILLIAM B. (Am Surg, 2011)
This report examines outcomes of revascularization for acute arterial mesenteric ischemia (AAMI) using the American College of Surgeons National Surgical Quality Improvement Program database. Patients with International Classification of Diseases, 9th Revision and Current Procedural Terminology codes indicating AAMI with concomitant mesenteric revascularization were identified. Demographic, risk factor, procedural, morbidity, and mortality data were examined. Associations with morbidity and mortality were analyzed by logistic regression. One hundred forty-two cases of AAMI were identified. Seventy-one cases were thrombotic and 71 were embolic according to revascularization codes. Mean age was 66 years, 84 per cent of patients were white, and 54 per cent were female. Unadjusted major morbidity and mortality rates were 69 and 30 per cent, respectively. Patients with thrombotic AAMI were more likely to have a lower body mass index, greater than 10 per cent weight loss in the past 6 months, and a history of smoking. Patients with embolic AAMI were more likely to present emergently with sepsis. Unadjusted morbidity and mortality rates were 78 and 38 per cent for embolic and 61 and 23 per cent for thrombotic AAMI, respectively. Multi-variable predictors of morbidity included bowel resection at the time of revascularization, transfer admission, and involvement of a surgical resident. Multivariable predictors of mortality included impaired functional status, increased age, and postoperative sepsis. Cause of AAMI was not a significant predictor of morbidity or mortality. In a large sample of AAMI cases, AAMI remained a highly lethal and morbid condition. Predictors of morbidity and mortality included indicators of advanced presentation, treatment delay, and patient-related factors specific to AAMI, including debility and advanced age. Efforts directed at prevention and increasing the speed of diagnosis and definitive treatment appear to be necessary to improve outcomes.